2001
DOI: 10.1046/j.1365-2141.2001.02992.x
|View full text |Cite
|
Sign up to set email alerts
|

Unrelated donor marrow transplantation in children with severe aplastic anaemia using cyclophosphamide, anti‐thymocyte globulin and total body irradiation

Abstract: Summary. We report a favourable outcome in 15 patients with severe aplastic anaemia (SAA) who were , 20 years of age and who underwent bone marrow transplantation (BMT) from a human leucocyte antigen (HLA)-matched unrelated donor. All patients were non-responders to intensive immunosuppressive therapy (IST) and were multiply transfused. The conditioning regimen consisted of cyclophosphamide (60 mg/kg/d, on d 24 and 23), antithymocyte globulin (2´5 mg/kg/d, on d 25 to 22) and total body irradiation (2´5 Gy  2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 34 publications
3
41
1
1
Order By: Relevance
“…7 In a separate pediatric study, this same group noted 33% severe GVHD. 21 Our results compare favorably to other series of pediatric BMT for SAA using URD. Margolis et al 22 reported 55% survival at 33 months with a similar approach, but graft rejection was higher in mismatched recipients.…”
Section: Discussionsupporting
confidence: 77%
“…7 In a separate pediatric study, this same group noted 33% severe GVHD. 21 Our results compare favorably to other series of pediatric BMT for SAA using URD. Margolis et al 22 reported 55% survival at 33 months with a similar approach, but graft rejection was higher in mismatched recipients.…”
Section: Discussionsupporting
confidence: 77%
“…31 In vivo or ex vivo T-cell depletion can effectively reduce the incidence and severity of GvHD, 1,10 but it may significantly delay T-cell reconstitution. 11,12 A number of different in vivo [32][33][34][35] and ex vivo 8 strategies have been used to deplete T cells from the graft. In our study, T cells were rigorously depleted (reduced by a factor of 10 3 -10 5 ) by positive selection of CD34 + hematopoietic progenitor cells with the CliniMACS-system.…”
Section: Discussionmentioning
confidence: 99%
“…13 Intensification of the preparative regimen by the addition of irradiation, either as limited field or total body irradiation to CY, has been advocated to minimize graft rejection. [5][6][7] The outcome of irradiation-based, alternative donor BMT has been variable. 4,8,9 Recent reports of unrelated donor BMT have been somewhat better.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors reported the inclusion of irradiation in the conditioning regimen. [5][6][7] While the rate of engraftment appeared to have increased, improvement in transplant outcome has been less impressive. [1][2][3][4]8,9 In addition, the shortand long-term side-effects of irradiation are of concern, especially in the pediatric age group.…”
mentioning
confidence: 99%